Modeling Lesson Planning with Authentic Materials for Preservice Teachers - Jasmin Alfonso-Vargas; Paola Ximena Romero Molina (Lenguaje)
Teacher educators worldwide have expressed their concern about teaching their students how to transfer theoretical knowledge into practice. Thus, this paper aims to describe a study about modeling lesson planning for 16 preservice teachers at a Colombian university program, featuring authentic materials (AM). It also shows the main perceptions of this group of teachers during the modeling workshops. To collect data, surveys, video recordings, student teachers’ activity samples, and a complete lesson plan was employed. In this action research, data were analyzed using thematic analysis. Findings revealed that following a structure such as pre, while, and post cycle was effective for student teachers to organize a lesson in terms of macro scaffolding. Meanwhile, they encountered challenges when proposing specific steps to accomplish the activities they sketched in a lesson plan. Similarly, these student teachers positively perceived the workshop sessions. This paper concludes by stating some pedagogical implications for further research and reflection.